Two Case Reports on Use of Prazosin for Drug Dreams. Issue 2 (March 2016) - Gopalakrishna, Ganesh; Popoola, Oluwole; Campbell, Austin; Nemetalla, Marina A.
Abstract : Substance abuse and dependence is estimated to cost roughly $700 billion annually including direct and indirect care in the United States. Drug dreams (DD), or using dreams, are a reportedly common phenomenon among patients with substance abuse, and have been postulated as triggers for relapse. Prazosin is an alpha-1 receptor antagonist originally approved by the United States Food and Drug Administration for the treatment of hypertension. Prazosin passes the blood brain barrier easily, contributing to central and cognitive effects. Prazosin's efficacy has been demonstrated in the management of posttraumatic stress disorder (PTSD), and associated nightmares. We present the cases of two patients with substance use disorder experiencing DD which resolved after the addition of prazosin during an acute psychiatric hospitalization. To our knowledge, this is the first time treatment of DD with prazosin has been reported in the literature. Both patients reported an alleviation of their DD after the medication was initiated. The effect was immediate and results were seen on the same night of the initial dose. The precise mechanism of this effect is unclear, but we hypothesize it is related to the decrease in noradrenaline effects at α-1 adrenoreceptors in the brain, similar to the effect on nightmares in PTSD. The key limitation is the low number of patients and lack of follow up presented in this report. No causal relationship can be established between the use of prazosin and resolution of DD in our patients.